Penerapan Model Pembelajaran Scramble untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Nurul Qamariah; Syifaul Gummah; Dwi Sabda Budi Prasetyo (IKIP Mataram, 2016)
This study aims to improve students' creative thinking skills through scramble learning models in physics science learning on the subject of heat at SMPN 4 Praya Barat Daya 2015/2016 Academic Year. The type of research used is Classroom Action Research (CAR). This research was conducted in two cycles. Each cycle consists of planning, carrying out observation and reflection. Data on creative thinking skills were obtained from the results of evaluating students' creative thinking skills using essay questions given to class VII students whose students were 35 students. The results of the study address an increase in creative thinking skills of class VII students of SMPN 4 Praya Barat Daya after learning using the scramble learning model. In the first cycle, the results of students' creative thinking ability were 57%, while the second cycle increased to 79% with creative criteria. Thus it can be concluded that the scramble learning model can improve students' creative thinking ability.